Кит - кораблик: стихи / Ирина Гурина ; худ. Н. Фаттахова - Гурина Ирина Валерьевна (Фламинго, 2009)
Экземпляры: ФО - 1; 7; (20110303) / Инвентарный номер: 46682 / Цена: 52.80 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Г 95 / ББК: 84(2Рос=Рус)6